EVALUASI FORMULASI PRODUK NUTRASETIKAL “POWDER DRINK” DARI EKSTRAK BUAH JERUK KUKU HARIMAU (Citrus medica L.) DAN UJI AKTIVITAS ANTIOKSIDANNYA DENGAN MENGGUNAKAN METODE DPPH (2,2-DIFENIL-1PIKRILHIDRAZIL) - Gultom, Roby; Amalia, Amalia (Universitas Imelda Medan, 2023)
Nutraceutical of powder drink products has been made from the fresh extracts of Tiger Nail’s fruits (Citrus Medica L). This research is a laboratory experimental. Fresh extracts were divided into FI (10%), FII (20%) and FIII (40%). The formulations were compounds of extracts, sucroses (sugars) and waters. Organoleptic’s test results were color is white, orange’s aroma, sweet taste and smooth textures. Hedonic’s test showed the color and aroma test of FII showed the panelists more like it (80% and 70%). The texture test of FIII showed the panelists like it very much (70%) and the taste test of FIII showed the panelists were very like it (60%). The pH values were ranged from 6-7. The fastest dissolving time test showed from FI (8 seconds). The highest viscosity test was showed by FIII (0.89 poise). The determination of vitamin C levels using UV-Vis Spectrophotometry showed FIII the highest levels of vitamin C (0.828%). But all antioxidants activity had low activity. FI has the highest IC50 value (51429005 ppm). Anova test value showed 0,005<0.05 that means the antioxidant activitywere significantly different. Tukey test showed the comparison of antioxidant properties between the formulations groups showed a significance value of 0.008 < 0.05.